Therapeutic Advancements in Multiple Myeloma - Gozzetti, Alessandro; Candi, Veronica; Papini, Giulia; Bocchia, Monica (Frontiers in Oncology, 2014)
Multiple myeloma survival has significantly improved in latest years, due to a broad spectrum of novel agents available for treatment. The introduction of thalidomide, bortezomib and lenalidomide together with autologous stem cell transplantation has dramatically prolonged complete remissions rate, progression free survivals resulting ultimately in prolonged survivals in myeloma patients. Moreover, novel strategies of treatment such as consolidation and maintenance are being used to implement responses. A number of new drugs such as carfilzomib and pomalidomide are already in clinical practice, and “new kids on the block” are entering, making the future of myeloma patients brighter.